Epitaxial Engineering Strategy to Amplify Localized Surface Plasmon Resonance and Electrocatalytic Activity Enhancement in Layered Bismuth Selenide by Phosphorus Functionalization. Issue 3 (18th January 2022) - Savariraj, Antonysamy Dennyson; Manikandan, Ramu; Raj, C. Justin; Velayutham, Rajavel; Mangalaraja, R. V.; Park, Jinsoo; Cho, Won‐Je; Kim, Byung Chul
Abstract: Bismuth selenide (Bi2 Se3 ) is an orderly layered material with large surface area and localized surface plasmon resonance (LSPR). The electrocatalytic profile of Bi2 Se3 has been least explore for energy storage applications since its pristine form is handicapped with limited electrical conductivity. Here we report an epitaxial engineering strategy to manipulate the weak van der Waals forces to expand the interlayer spacing by intercalating phosphorus (P) atom by chemical vapor deposition (CVD) method. The obtained P intercalated Bi2 Se3 (P@Bi2 Se3 ) exhibited towering LSPR, increased carrier density bestowing ample active sites, enhanced ion diffusion and plentiful channels for the exodus of electrolyte. The potential of P@Bi2 Se3 was examined for energy storage application which exhibited battery like behavior with a specific capacity ( C s ) of 194 C g −1 at 3 A g −1 current density against 121 C g −1 by Bi2 Se3 /NF under identical condition and restored 88 % of its initial specific capacity even after 5000 charge/discharge cycles. The hybrid supercapacitor (HSC) assembled using P@Bi2 Se3 and O, N, S@AC as positive and negative electrodes exhibited a considerable specific capacitance, high specific energy ( E s ) and specific power ( P s ) with excellent stability for 10000 charge/discharge cycles. The surface and interfacial engineering strategy proposed here can be extended to tune plasmonic resonance and charge carrier energy density for the successful implementation of Bi2 Se3 beyond energy storage applications. Abstract : Towards more active sites and channels : An epitaxial engineering strategy is reported to manipulate the weak van der Waals forces to obtain phosphorus intercalated Bi2 Se3 (P@Bi2 Se3 ), which exhibits battery like behavior and works excellently as positive electrodes for supercapacitors.